A new thermoanalytical method for the quantification of microplastics in industrial wastewater. (April 2020) - Mallow, Ole; Spacek, Stefan; Schwarzböck, Therese; Fellner, Johann; Rechberger, Helmut
Abstract: Plastics are crucial for our modern lifestyle and yet pose a major threat to our environment. Rising levels of microplastics (MP) in rivers and oceans are a big challenge for our economy and regulatory institutions as well as from a scientific point of view. Smaller microplastic particles, in particular, are especially hard to identify and even harder to quantify in environmental samples. Hence, we present a novel and inexpensive approach to quantify microplastics (MP) on a weight basis, relying on a thermoanalytical method. The Elemental Analysis combined with Overdetermined Equation Method (EA-OEM) was originally developed for determining the plastic content of refuse-derived fuels. It makes use of the distinct differences in the organic elemental composition (C, H, N, S, O) of plastics, biogenic and inorganic materials to calculate the (micro)plastic content on a detailed weight base. The study presented provides the first experimental results yielded from the application of the EA-OEM and two different laboratory approaches to the analysis of polyethylene (PE) and polypropylene (PP) MP content in industrial effluent samples from one source. In this way, it was possible to ensure that the polymer composition was known and the MP content therein (10–29%) could be derived. Further, the study reveals good MP recovery rates when applying the methodology to PE/PP-spiked samples. Graphical abstract: Image 1 Highlights: Microplastic quantification without lower particle size limit. Quantification based on elemental analysis of the parameters C, H, N, S and O. Comparison of a direct treatment and an oxidative treatment method. Verification of the results with polymer spiked samples. Abstract : This study provides the first results yielded from the application of an Elemental Analysis combined with Overdetermined Equation Method to quantify microplastic content.